Pengaruh Genre Film, Popularitas Aktor, dan Review Media Sosial Terhadap Keputusan Menonton Film Agak Laen - Ilham Hermi Setiawan; Suhaji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of film genre, actor popularity, and social media reviews on the decision to watch the film Agak Laen in cinemas in Semarang. This research is relevant as emotional and digital factors increasingly influence consumer behavior, especially among younger audiences. The findings are expected to contribute to consumer behavior theory and serve as a practical reference for film industry stakeholders. A quantitative approach with a descriptive correlational method was used. Data were collected through questionnaires from 100 respondents and analyzed using multiple linear regression with the help of SPSS version 26. The results indicate that, partially, film genre and social media reviews have a positive and significant effect on viewing decisions, while actor popularity does not. However, all three variables together have a significant simultaneous effect. These findings highlight the importance of combining creative content and digital strategies to attract audiences.